Covalent organic framework membrane based on biomimetic mineralization strategy, preparation method and application of covalent organic framework membrane in ion separation

By introducing functional groups such as methoxy and polymer materials into the covalent organic frame membrane, the separation problem of lithium ions and magnesium ions is solved, and the efficient Li+/Mg2+ separation effect is achieved, showing the extraction of salt lake brine Technical breakthrough.

CN119303452AActive Publication Date: 2025-01-14CHINA THREE GORGES UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411326236.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-14
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively separate lithium ions (Li+) and magnesium ions (Mg2+) due to their similar physical and chemical properties, making it difficult to separate during the extraction process, especially in the extraction of lithium resources in salt lake brine.

Method used

The covalent organic frame membrane (COF) design is adopted based on the bionic mineralization strategy. By introducing functional groups such as methoxy groups and crown ethers on the surface or inside the COF membrane, the pore size and structural stability of the membrane are regulated, and a variety of polymers are combined. The use of materials, such as polyacrylonitrile (PAN), polyethylene terephthalate (PET), etc., forms a film material with high selectivity and high permeability.

Benefits of technology

It significantly improves the selective transmission performance of Li+, effectively reduces the permeability of Mg2+, improves the selectivity and efficiency of Li+/Mg2+ separation, and is suitable for efficient and environmentally friendly ion separation processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303452A_ABST
    Figure CN119303452A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of a covalent organic framework membrane based on a biomimetic mineralization strategy and application of the covalent organic framework membrane in ion separation. In the separation process of the monovalent ions, the methoxyl forms stable interaction with the monovalent ions through the unique coordination characteristic and electronegativity of the methoxyl, so that the transmission rate of the monovalent ions is remarkably improved. And meanwhile, the introduction of the functionalized methoxyl can effectively inhibit the passing of divalent ions, so that efficient ion separation is realized. According to the biomimetic mineralization strategy, the organic polymer and the COF are compounded, so that the mechanical strength and the chemical stability of the COF membrane can be remarkably improved. Compared with a traditional separation membrane, the biomimetic mineralized COF membrane provided by the invention shows higher separation efficiency, more excellent selectivity and longer service life, and is suitable for efficient extraction of monovalent ion resources such as lithium, preparation of battery materials and ion separation application in related industrial production processes. The functionalized methoxy COF membrane material has the advantages of adjustable structure, simple preparation, large-scale production potential and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to preparation and application of a covalent organic framework membrane based on a bionic mineralization strategy, and belongs to the technical field of covalent organic framework membranes. Background Art

[0002] Monovalent ions (Li + 、Na + , K + Lithium (Mg) is an important strategic resource for modern energy and technology industries, and a key raw material for the preparation of high-energy density batteries. Its demand has increased significantly with the rapid growth of markets such as electric vehicles and portable electronic devices. However, the extraction of monovalent ions is still challenging. For example, in the development of lithium resources, salt lake brine extraction is the main mining method because salt lake extraction has the advantages of low development cost, low environmental damage, and high economic benefits. Lithium resources in salt lake brine are usually accompanied by magnesium ions (Mg 2+ ), due to Mg 2+ With Li + The physical and chemical properties of Li are similar, especially the ionic radius and hydrate structure are similar, so it is difficult to effectively separate them during the extraction process. In recent years, membrane separation technology has become a solution to Li due to its high efficiency, high selectivity and environmental protection. + / Mg 2+ A potential solution to separation problems. Compared with traditional separation methods, membrane separation technology can achieve highly selective separation of target ions by precisely controlling the pore size, surface chemical properties and functional modification of membrane materials. Covalent organic framework (COF) membranes have become a popular choice for Li+ due to their high porosity, high stability and high adjustability. + / Mg 2+ The research hotspot in the separation field. By functionalizing the COF membrane, such as introducing methoxyl groups, crown ethers and other functional groups, the Li + selective transport and reduce the membrane's sensitivity to Mg 2+ The nature regulates the mineralization process through polymers, thus forming a hardened material with high stability and high density. This phenomenon provides a new guiding idea for the transformation of COF from a solution phase monomer to a solid phase membrane. By uniformly introducing organic molecules on the surface or inside the COF membrane, it is expected to enhance the structural stability of the membrane, control the defects of the membrane, and develop a new membrane separation material with high selectivity and high permeability, which will provide a new opportunity for Li + / Mg 2+ The plasma separation process has revolutionized the process. Summary of the invention

[0003] According to the above technical background, the present invention provides a design and preparation method of a covalent organic framework membrane based on a biomimetic mineralization strategy.

[0004] The present application relates to the preparation and application of a covalent organic framework (COF) membrane material. COF is a type of crystalline porous material with a highly ordered structure, which is formed by organic ligand molecules connected by covalent bonds. The structural design of COF materials is highly adjustable, and different combinations of organic units give COF membranes different pore characteristics and pore sizes. Therefore, it can be precisely designed and customized according to specific application requirements, making COF membranes show a wide range of application potential in the separation field.

[0005] A design and preparation of a covalent organic framework membrane based on a biomimetic mineralization strategy, the preparation method comprising the following steps: Step 1: dissolving the aldehyde monomer in an organic solvent and adding a catalyst to obtain solution 1; dissolving the amino monomer in deionized water to obtain solution 2.

[0006] Step 2: Place the basement membrane in the middle of the H-type diffusion cell and fix the two sides of the diffusion cell with metal clips. Add solution 1 to the diffusion cell facing the front of the basement membrane and add solution 2 to the diffusion cell facing the back. Seal the diffusion cell and let it react for a while under constant conditions.

[0007] Step 3: After the reaction is completed, remove the COF film, clean its surface, and place it at room temperature for later use.

[0008] The aldehyde monomer in step 1 is selected from one of 2,4,6-triformylphloroglucinol and 1,3,5-trimethoxy-2,4,6-triformylbenzene, and the amount of the selected monomer is 0.01 mmol-0.1 mmol.

[0009] The organic solvent is selected from dichloromethane, mesitylene, dimethyl sulfoxide, anisole, and ethyl acetate. The volume of the solvent is preferably 5-50 mL to achieve complete solvent of the monomer. The catalyst used can be selected from the group consisting of octanoic acid, acetic acid, concentrated hydrochloric acid (35-37%), and concentrated sulfuric acid (93-98%), with a concentration of 1 mol / L-10 mol / L.

[0010] The amino monomer is selected from 2,5-diaminoanisole, 2,5-dimethoxy-p-phenylenediamine and p-phenylenediamine. The amount of the selected monomer is 0.01 mmol-0.1 mmol. The volume of the deionized water used is 5-50 mL.

[0011] When the aldehyde monomer and the amino monomer are combined, the aldehyde monomer contains a methoxy group. In addition, the combination of p-phenylenediamine and 2,4,6-triformylphloroglucinol is used as a control experiment.

[0012] The amount of PEI added to the solution is determined according to the mass of the amino monomer, ranging from 1% to 30% of the mass of the amino monomer, wherein the preferred amount added is 10-20% of the mass of the amino monomer, and more preferably 10%. The molecular weight of the selected PEI ranges from 1000 to 50000 Da to ensure that the formed membrane has a high degree of continuity and chemical stability; wherein, PEI with a molecular weight of 10000 Da is preferred. During the preparation process, PEI can be flexibly added to either side of the diffusion cell according to the characteristics of the base membrane: the hydrophobic base membrane is added to the solution 1 side on the front side of the base membrane, or the solution 2 side on the back side of the hydrophilic base membrane, both of which can play their functions.

[0013] The base film material used in step 2 can be selected from a variety of polymer materials such as polyacrylonitrile (PAN), polysulfone (PSU), polyethylene terephthalate (PET), polyamide (PA), polytetrafluoroethylene (PTFE), etc. The above-mentioned base film materials each have their own characteristics and can provide excellent mechanical strength, chemical stability and interface compatibility under different operating conditions. The specific base film material selected can be optimized according to the needs of the final application. In this preparation method, the constant reaction condition is to control the temperature to ensure the stability of the mineralization process and the uniform deposition of minerals. The reaction temperature range can be adjusted between 20°C and 100°C, with 50-60°C being the preferred temperature. The static reaction time can be adjusted between 1 and 5 days, and the preferred static time is 2-4 days. During this time, the continuity of the COF membrane can be ensured, while avoiding performance degradation caused by excessive or insufficient reaction.

[0014] In some preferred embodiments, the selection of amino and aldehyde monomers must contain a type of monomer with a methoxy group. When the monomers are selected for preparation, when the aldehyde monomer is 2,4,6-triformylphloroglucinol and the amino monomer is 2,5-diaminoanisole, the corresponding COF film is TpPaOCH3@PEI (10 w%), where w% is the percentage of the mass of PEI to the mass of the amino monomer. For example, if the mass of PEI is 10% of the mass of the amino monomer, it is recorded as 10 w%.

[0015] In some preferred embodiments, when the aldehyde monomer is 2,4,6-triformylphloroglucinol and the amino monomer is 2,5-dimethoxy-p-phenylenediamine, the corresponding COF film is TpPa(OCH3)2@PEI (10 w%), where w% is the percentage of the mass of PEI to the mass of the amino monomer. For example, if the mass of PEI is 10% of the mass of the amino monomer, it is recorded as 10 w%.

[0016] In some preferred embodiments, when the aldehyde monomer is 2,4,6-triformylphloroglucinol and the amino monomer is p-phenylenediamine, the corresponding COF film is TpPa (10 w%), wherein w% is the percentage of the mass of PEI to the mass of the amino monomer. For example, if the mass of PEI is 10% of the mass of the amino monomer, it is recorded as 10 w%.

[0017] In some preferred embodiments, when 1,3,5-trimethoxy-2,4,6-triformylbenzene and the amino monomer is p-phenylenediamine, the corresponding COF film is TMFBPa@PEI (10 w%), wherein w% is the percentage of the mass of PEI to the mass of the amino monomer. For example, the mass of PEI is 10% of the mass of the amino monomer, then it is recorded as 10 w%.

[0018] Another technical solution of the present invention is to provide a COF membrane based on biomimetic mineralization, wherein the COF layer is formed by polymerization of amino monomer units and aldehyde monomer units, wherein the aldehyde monomer units and the amino monomer units are respectively added to both sides of the base membrane and diffuse to the positive surface of the base membrane to undergo polymerization reaction.

[0019] The monomer in the aldehyde monomer unit is selected from one of 2,4,6-triformylphloroglucinol and 1,3,5-trimethoxy-2,4,6-triformylbenzene.

[0020] The monomer in the amino monomer unit is selected from any one of 2,5-diaminoanisole, 2,5-dimethoxy-p-phenylenediamine and p-phenylenediamine.

[0021] In the above example, the combination of p-phenylenediamine and 2,4,6-triformylphloroglucinol is a control experiment.

[0022] When the base membrane is a hydrophobic base membrane, the aldehyde monomer is dissolved in an organic solvent and applied to the front of the hydrophobic base membrane, and an aqueous solution is added to the other side. If the base membrane is a hydrophilic base membrane, the amino monomer is dissolved in an aqueous solution and applied to the front of the hydrophilic base membrane. In the hydrophobic base membrane, PEI is preferably added to the solution side corresponding to the front of the base membrane, while in the hydrophilic base membrane, PEI is preferably added to the back to give full play to its role in promoting the stability of the membrane structure and improving the separation performance.

[0023] In some specific embodiments, the raw materials of the amino monomer unit also include a mixed solution formed by adding a catalyst to an organic solvent, wherein the organic solvent is selected from any one of dichloromethane, mesitylene, dimethyl sulfoxide, anisole, and ethyl acetate, and the catalyst used can be selected from one of octanoic acid, acetic acid, hydrochloric acid (35-37%), and sulfuric acid (93-98%).

[0024] The dosage of the aldehyde monomer is 0.01 mmol-0.1 mmol, and the catalyst concentration is 1 mol / L-10 mol / L; the dosage of the amino monomer is 0.01 mmol-0.1 mmol.

[0025] The base film material is selected from any one of polyacrylonitrile PAN, polysulfone PSU, polyethylene terephthalate PET, polyamide PA, and polytetrafluoroethylene PTFE.

[0026] The process of interfacial polymerization of the aldehyde monomer units and the amino monomer units on both sides of the base film refers to the process of dipping and letting the monomer units of the base film diffuse at two times at a certain temperature.

[0027] In some embodiments, the diffusion temperature is adjusted between 20°C and 100°C, with 60-80°C being the preferred temperature; the static reaction time can be adjusted between 1 and 5 days, with the preferred static reaction time being 2-4 days.

[0028] In some embodiments, in the biomimetic mineralized COF film of the present invention, the COF layer is characterized by an X-ray diffraction (XRD) 2θ value including a characteristic peak at about 5°±0.2°, indicating that the COF film has an ordered crystal structure.

[0029] The X-ray diffraction (XRD) 2θ also includes 27 o The characteristic peak of ±0.4° represents the stacking effect of the crystalline structures between COFs.

[0030] Another technical solution of the present invention is to provide a new use of a biomimetic mineralized COF membrane, based on the application of the biomimetic mineralized COF membrane in ion separation, wherein the ions include potassium ions, sodium ions, lithium ions, magnesium ions, and calcium ions. Two or more ion separations. The metal salt used is a halide, including chloride, bromide, and iodide. When separation is performed, the metal salt is ensured to be the same type of halide.

[0031] In some embodiments, the halide concentration of 0.05-0.5 mol / L can achieve membrane separation effect.

[0032] In the technical solution of the present invention, in the separation of monovalent / divalent ions, such as Li + / Mg 2+ During the separation process, the introduction of oxygen-containing groups (such as methoxy, crown ether, etc.) can significantly improve the separation performance. + Due to its small radius and high charge density, it interacts strongly with oxygen-containing groups, thus promoting Li + Although Mg 2+ Has a higher charge number, but due to its larger ionic radius, the charge density is lower than that of Li+ , and its high hydration degree makes Mg 2+ The coordination effect with oxygen-containing groups is weak. In addition, the introduction of oxygen-containing groups also leads to a moderate reduction in the pore size of the COF membrane, which further inhibits the Mg with a larger hydration radius. 2+ The transport efficiency of the membrane to Li + Based on this mechanism, the present invention prepares a COF membrane with functionalized methoxy groups. The introduction of methoxy groups significantly improves the selectivity of Li + The transmission rate of Mg 2+ The diffusion rate of COF membranes is increased by 1.5 wt%. At the same time, by introducing PEI as a regulator in the preparation process of COF membranes, the growth process of COF membranes is regulated, which significantly improves the stability of the membranes. PEI can not only provide abundant amino sites in the membrane formation process, but also form strong chemical bonds with the organic matrix in the COF membrane, enhancing the stability and continuity of the membrane. Under harsh operating conditions, such as high temperature and strong acid and alkali environments, the membrane still maintains structural integrity.

[0033] Through the strategy of bionic mineralization, polymer regulation is introduced in the COF film formation process to repair intercrystalline defects and reduce the reaction energy barrier; at the same time, methoxy functional groups are modified on the COF pore walls to enhance the membrane's selective transport performance for monovalent ions.

[0034] The present invention relates to a COF membrane design and preparation based on a biomimetic mineralization strategy, and the introduction of methoxy groups significantly improves the separation effect of the membrane material on monovalent / divalent ions. + and Mg 2+ As an example of the selective separation of Li + / Mg 2+ The membrane is used to separate Li + The formation of a relatively close interaction promotes the Li + The rapid transmission of Mg 2+ Due to the larger radius and lower charge density, the interaction with methoxy groups is weaker, resulting in a significant decrease in the transport rate. Compared with the traditional separation method, the methoxy COF membrane prepared by the present invention exhibits higher selectivity and stability, and is suitable for efficient and environmentally friendly Li + / Mg 2+ The method is simple and feasible, and the prepared membrane material is uniform and dense, which has a wide range of application prospects and is expected to become a Li + / Mg 2+ Important technological breakthrough in the field of separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1The scanning electron microscope surface and cross-sectional images of the embodiments TMFBPa@PEI (10 w%), TpPa(OCH3)2@PEI (10 w%), and TpPaOCH3@PEI (10 w%) are shown in Figures 1a and 1b respectively, which are the surface and cross-sectional images of TMFBPa@PEI (10 w%). Figure 1 c and d are surface and cross-sectional electron micrographs of TpPa(OCH3)2@PEI (10 w%). Figure 1 e and f are surface and cross-sectional electron micrographs of TpPaOCH3@PEI (10 w%).

[0036] Figure 2 The infrared spectra of the embodiments TMFBPa@PEI (10 w%), TpPa(OCH3)2@PEI (10 w%), and TpPaOCH3@PEI (10w%) are shown in FIG. Figure 2 a is the infrared image of TMFBPa@PEI (10 w%), Figure 2 b is the infrared image of TpPa(OCH3)2@PEI (10 w%), Figure 2 c is the infrared image of TpPaOCH3@PEI (10 w%).

[0037] Figure 3 These are the XRD spectra of Examples TMFBPa@PEI (10 w%), TpPa(OCH3)2@PEI (10 w%), and TpPaOCH3@PEI (10 w%), from top to bottom, respectively: TMFBPa@PEI (10 w%), TpPa(OCH3)2@PEI (10 w%), and TpPaOCH3@PEI (10 w%).

[0038] Figure 4 The BET pore size analysis diagram of the embodiments TMFBPa@PEI (10 w%), TpPa(OCH3)2@PEI (10 w%), and TpPaOCH3@PEI (10w%), wherein Figure 4 a is the pore size distribution diagram of TMFBPa@PEI (10 w%), Figure 4 b is the pore size distribution diagram of TpPa(OCH3)2@PEI (10 w%), Figure 4 c is the pore size distribution diagram of TpPaOCH3@PEI (10 w%).

[0039] Figure 5 The present invention shows that Li + / Mg 2+ Comparison results of separation performance. DETAILED DESCRIPTION

[0040] The specific implementation of the present invention is further described in conjunction with the accompanying drawings. The specific embodiments described are only used to explain the principles and implementation processes of the present invention and do not constitute a limitation of the present invention.

[0041] Example 1: Preparation of TMFBPa@PEI (10 w%) membrane, the steps are as follows: Step 1: Dissolve 0.5 mmol of 1,3,5-trimethoxy-2,4,6-triformylbenzene in 15 mL of anisole and add 0.1 mL of n-octanoic acid. Dissolve 0.75 mmol of p-phenylenediamine in 15 mL of deionized water. Ultrasonic disperse the two solutions for 2 min and set aside.

[0042] Step 2: Place the polyacrylonitrile-based membrane between the diffusion cells and fix it with a metal clip. Pour the dispersed anisole solution into the diffusion cell on the front of the polyacrylonitrile membrane, pour the aqueous solution into the diffusion cell on the other side, and add PEI with a mass percentage of 10% of the amino monomer. Transfer the diffusion cell to a 60°C oven and let it react for 4 days. After the reaction is completed, take out the COF membrane, wash it three times with ethanol and deionized water, and dry it at room temperature to obtain the TMFBPa@PEI (10 w%) membrane.

[0043] Figure 1 a and b show the scanning electron microscopy images of the surface morphology and cross-sectional structure of the TMFBPa@PEI (10 w%) film, respectively. It can be seen from the figure that the surface of the prepared TMFBPa@PEI (10 w%) film is flat and has no obvious defects, and the film thickness is uniform. Figure 2 a is the infrared spectrum of TMFBPa@PEI (10 w%) film, where the - The characteristic peak at ¹ corresponds to the vibration of the CO bond, indicating that the methoxy-functionalized COF has been successfully synthesized. - ¹ is the stretching vibration peak of -NH, indicating the successful compounding of PEI. Figure 3 The XRD pattern of TMFBPa@PEI (10 w%) film is shown. The diffraction peak near 5° reflects that the COF film has high crystallinity, confirming the formation of long-range ordered pore structure in the TMFBPa@PEI (10 w%) film. Figure 4 a shows the BET pore size distribution of TMFBPa@PEI (10 w%) membrane, and the results show that the membrane has the smallest pore structure, further proving that the introduction of methoxy groups effectively reduces the pore size of the COF membrane.

[0044] Example 2: Preparation of TpPa(OCH3)2@PEI (10 w%) membrane. The steps are basically the same as those in Example 1, except that 1,3,5-trimethoxy-2,4,6-triformylbenzene in step 1 is replaced with 2,4,6-triformylphloroglucinol, and p-phenylenediamine is replaced with 2,5-dimethoxyp-phenylenediamine. The other steps remain the same.

[0045] Figure 1 c and d show the surface and cross-sectional electron micrographs of the TpPa(OCH3)2@PEI (10 w%) membrane, respectively. It can be seen from the figure that the surface of the prepared TpPa(OCH3)2@PEI (10 w%) membrane is smooth and has no obvious defects, and the thickness of the membrane is uniform. Figure 2 b is the infrared spectrum of TpPa(OCH3)2@PEI (10 w%) film, where the - The peak at ¹ corresponds to the characteristic of CO bond, indicating the successful preparation of methoxy-functionalized COF. - ¹ is the stretching vibration peak of -NH, indicating the successful compounding of PEI. Figure 3 This is the XRD pattern of the TpPa(OCH3)2@PEI (10 w%) film, in which the peak at around 5° shows that the COF film has high crystallinity, proving that the TpPa(OCH3)2@PEI (10 w%) film forms a long-range ordered pore structure. Figure 4 b is the BET pore size distribution diagram of TpPa(OCH3)2@PEI (10 w%) membrane, which shows that the membrane has a smaller pore structure, but its pores are larger than those of TMFBPa@PEI (10 w%) membrane, indicating that the number of AX groups introduced will significantly affect the pore size of the COF membrane. The more the number, the smaller the pore size.

[0046] Example 3: Preparation of TpPaOCH3@PEI (10 w%) membrane. The steps are basically the same as those in Example 1, except that 1,3,5-trimethoxy-2,4,6-triformylbenzene in step 1 is replaced with 2,4,6-triformylphloroglucinol, and p-phenylenediamine is replaced with 2,5-diaminoanisole. The other steps remain the same.

[0047] Figure 1 c and d show the surface morphology and cross-sectional structure of the TpPaOCH3@PEI (10 w%) membrane, respectively. It can be observed from the figure that the prepared TpPaOCH3@PEI (10 w%) membrane has a smooth surface without obvious defects, and the thickness of the membrane is uniform. Figure 2 c is the infrared spectrum of TpPaOCH3@PEI (10 w%) film, where the -The peak at ¹ corresponds to the characteristic vibration peak of the CO bond, verifying that the methoxy group was successfully introduced into the COF structure. - ¹ is the stretching vibration peak of -NH, indicating the successful compounding of PEI. Figure 3 Figure 2 is the XRD pattern of TpPaOCH3@PEI (10 w%) film, which shows a diffraction peak at about 5°, indicating that the COF film has high crystallinity and long-range ordered pore structure. Figure 4 a is the BET pore size distribution diagram of TpPaOCH3@PEI (10 w%) membrane. The results show that the membrane has a relatively small pore structure, but the pore size is larger than that of TMFBPa@PEI (10 w%) membrane and TpPa(OCH3)2 membrane, which further indicates the influence of the amount of methoxy group introduction on the pore size of COF membrane. As the number of methoxy groups increases, the pore size tends to decrease.

[0048] Example 4: Preparation of TpPa@PEI (10 w%) membrane, the steps are basically the same as those in Example 1, except that 1,3,5-trimethoxy-2,4,6-triformylbenzene in step 1 is replaced with 2,4,6-triformylphloroglucinol, and the other steps remain the same. Figure 5 shown.

[0049] Example 5: Preparation of polyacrylonitrile (HPAN) membrane. In step 1, no amino and aldehyde monomers were added. The other conditions were the same as those in Example 1. The separation performance was as follows: Figure 5 shown.

[0050] Step 3: Perform ion separation test.

[0051] The ion separation test is carried out using an H-type electrolytic cell. This experimental device is currently the most commonly used ion self-diffusion separation test system. The diffusion rate of ions is determined by connecting a conductivity meter. In the device, the diffusion cell is divided into a feed side and a diffusion side. The feed side is filled with a certain volume of the salt ion solution to be tested, with the concentration set to 0.1 mol / L, while the diffusion side is filled with an equal volume of deionized water. At preset time intervals, the conductivity change on the diffusion side is measured, and the concentration of ions diffused to the diffusion side is calculated based on these data. The diffusion rate of ions can be calculated based on the concentration change within a constant time. The separation effect is evaluated by the separation factor, which is the ratio of the two ion diffusion rates. For example, testing Na + With Li + When the separation effect is desired, sodium ions and Li + The diffusion rate of Na + The diffusion rate of Li + The diffusion rate of Na + / Li +Separation factor. The larger the separation factor, the more significant the separation effect.

[0052] The test results according to the above embodiment are as follows Figure 4 As shown. Among all the tested membranes, the MFBPa@PEI (10 w%) membrane with three methoxy groups exhibited the best lithium-magnesium separation performance. The second was the TpPa(OCH3)2@PEI (10 w%) membrane with two methoxy groups and the TpPaOCH3@PEI (10 w%) membrane with one methoxy group, while the TpPa@PEI (10 w%) membrane without methoxy groups exhibited poor separation effect. This indicates that the number of methoxy groups has an important effect on the separation of COF membranes in Li + / Mg 2+ The performance in separation is significantly affected. Compared with the traditional TpPa@PEI (10 w%) membrane without methoxy groups, increasing the number of methoxy groups can effectively improve the separation performance of the membrane. This result highlights the importance of methoxy functionalization in COF membrane design and provides new ideas for the development of high-performance ion separation membranes in the future.

[0053] Separation performance Figure 5 Among them, the TMFBPa@PEI (10 wt%) composite membrane with the highest methoxy content showed the best Li + / Mg 2+ Separation effect. As the methoxy content in the membrane gradually decreases, Li + / Mg 2+ The separation performance decreased significantly, which indicates that the methoxyl group is important for promoting the + It plays a significant role in transport and can effectively inhibit Mg 2+ Compared with the COF membrane without methoxy groups, the latter has a Li + / Mg 2+ The separation capacity is extremely low and has almost no separation effect. + / Mg 2+ The separation performance is even worse, further confirming that COF membranes are + / Mg 2+ It played a major role in the separation process, demonstrating the key role of methoxy functionalization in improving separation performance.

[0054] Although the above description is combined with the accompanying drawings to explain the present invention in detail, the present invention is not limited to the specific embodiments shown. These embodiments are only examples and are not restrictive. After understanding the basic principles of the present invention, those skilled in the art can make various modifications and adjustments without departing from the core idea of ​​the invention, and these modifications and adjustments should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a covalent organic framework membrane based on a biomimetic mineralization strategy, characterized in that: The steps include: Step 1: dissolving the aldehyde monomer in an organic solvent and adding a catalyst to obtain solution 1; dissolving the amino monomer in deionized water and fully dispersing the mixture to obtain solution 2; Step 2: sandwich the basement membrane between the H-type diffusion cells, add solution 1 to the diffusion cell facing the front of the basement membrane, add solution 2 to the diffusion cell facing the back, and then add a certain equivalent of polyethyleneimine to the diffusion cell; seal the diffusion cell and let it react for a period of time under constant conditions; Step 3: After the reaction is completed, remove the COF film, clean its surface, and place it at room temperature for later use.

2. The method for preparing a covalent organic framework membrane based on a biomimetic mineralization strategy according to claim 1, characterized in that: The aldehyde monomer in step 1 is selected from one of 2,4,6-triformyl phloroglucinol and 1,3,5-trimethoxy-2,4,6-triformylbenzene; the organic solvent is selected from any one of dichloromethane, mesitylene, dimethyl sulfoxide, anisole, and ethyl acetate; the catalyst used can be selected from one of n-octanoic acid, acetic acid, concentrated hydrochloric acid, and concentrated sulfuric acid; the amount of the aldehyde monomer is 0.01 mmol-0.1 mmol, and the catalyst concentration is 1 mol / L-10 mol / L; The amino monomer is selected from any one of 2,5-diaminoanisole, 2,5-dimethoxy-p-phenylenediamine and p-phenylenediamine; the amount of the amino monomer used is 0.01 mmol-0.1 mmol.

3. The method for preparing a covalent organic framework membrane based on a biomimetic mineralization strategy according to claim 1, characterized in that: In step 2, PEI is added to the solution, and the amount thereof is determined according to the mass of the amino monomer, ranging from 1% to 30% of the mass of the amino monomer, wherein the preferred amount is 10% of the mass of the amino monomer; the molecular weight of the selected PEI ranges from 1000 to 50000 Da.

4. The method for preparing a COF membrane based on biomimetic mineralization according to claim 1, characterized in that: The base film material described in step 2 is selected from any one of polyacrylonitrile PAN, polysulfone PSU, polyethylene terephthalate PET, polyamide PA, and polytetrafluoroethylene PTFE.

5. The method for preparing a COF membrane based on biomimetic mineralization according to claim 1, characterized in that: The reaction temperature range can be adjusted between 20°C and 100°C, with 50-60°C being the preferred temperature; the reaction standing time can be adjusted between 1 and 5 days, with the preferred standing time being 2-4 days.

6. A COF membrane based on biomimetic mineralization, characterized in that: The COF layer is formed by amino monomer units and aldehyde monomer units, wherein the aldehyde monomer units and the amino monomer units are added to both sides of the base film respectively and diffuse to the front surface of the base film to undergo polymerization reaction.

7. The COF membrane based on biomimetic mineralization according to claim 6, characterized in that: The aldehyde monomer units are interfacially polymerized on the hydrophobic side surface of the base film; the amino monomer units are interfacially polymerized on the hydrophilic side surface of the base film, and both sides of the base film contain polyethyleneimine.

8. The COF membrane based on biomimetic mineralization according to claim 7, characterized in that: The COF layer is characterized by an X-ray diffraction (XRD) 2θ value including a characteristic peak at about 5°±0.2°.

9. A biomimetic mineralized COF membrane for ion separation, characterized in that: It comprises the biomimetic mineralized COF membrane prepared by the preparation method according to any one of claims 1 to 5 or the COF membrane based on biomimetic mineralization according to any one of claims 6 to 8.

10. The use of the COF membrane based on biomimetic mineralization in ion separation according to claim 9, characterized in that: The ions include potassium ions, sodium ions, lithium ions, magnesium ions, calcium ions, or two or more ions to be separated. The metal salts used are halides, including chlorides, bromides, and iodides, and the metal salts are ensured to be of the same type of halide during separation.

Citation Information

Patent Citations

  • Proton exchange membrane and preparation method and application thereof

    CN112510236A

  • Preparation and application methods of high-permeability selective ion separation membrane

    CN115501763A

  • Preparation and application method of selective electrodialysis ion separation membrane

    CN116116252A

  • Polyelectrolyte / covalent organic framework nanosheet hybrid membrane as well as preparation method and application thereof

    CN116236918A

  • Preparation of COF / MXene membrane with mixed dimension pore channels and application of COF / MXene membrane in water treatment

    CN117753228A